Pygoscelis adeliae - Hospitaleche, Carolina Acosta; Soto-Acuña, Sergio (Zenodo, 2023)
Pygoscelis adeliae (MLP 32, MLP 33, MLP 415, MLP 416, MLP 417, MLP 418, MLP 419, MLP 420, MLP 421, MLP 422, MLP 423, MLP 424, MLP 425, MLP 426, MLP 427, MLP 428, MLP 429, MLP 430, MLP 431, MLP 432, MLP 433, MLP 434. MLP 464), Published as part of Hospitaleche, Carolina Acosta & Soto-Acuña, Sergio, 2023, A small penguin cranium (Aves, Spheniscidae) from the Late Miocene of Bahía Inglesa Formation, Atacama Desert, Northern Chile, pp. 233-244 in Comptes Rendus Palevol 22 (13) on page 237, DOI:10.5852/cr-palevol2023v22a13, http://zenodo.org/record/14233130